2016
DOI: 10.1104/pp.16.00829
|View full text |Cite
|
Sign up to set email alerts
|

Herbaceous angiosperms are not more vulnerable to drought-induced embolism than angiosperm trees

Abstract: The water transport pipeline in herbs is assumed to be more vulnerable to drought than in trees due to the formation of frequent embolisms (gas bubbles), which could be removed by the occurrence of root pressure, especially in grasses. Here, we studied hydraulic failure in herbaceous angiosperms by measuring the pressure inducing 50% loss of hydraulic conductance (P 50 ) in stems of 26 species, mainly European grasses (Poaceae). Our measurements show a large range in P 50 from 20.5 to 27.5 MPa, which overlaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(123 citation statements)
references
References 44 publications
9
112
0
2
Order By: Relevance
“…Our finding of a positive association between SSG and riparian zone aridity for communities containing a mixture of woody and herbaceous plants, as well as in separate analyses for herbaceous species (McCoy-Sulentic et al 2017, written communication), strongly suggest a role of high SSG in adaptation of herbaceous plants to water stress (e.g. Lens et al 2016) in addition to woody plants that have been featured in most previous investigations.…”
Section: Stem Specific Gravitymentioning
confidence: 55%
See 1 more Smart Citation
“…Our finding of a positive association between SSG and riparian zone aridity for communities containing a mixture of woody and herbaceous plants, as well as in separate analyses for herbaceous species (McCoy-Sulentic et al 2017, written communication), strongly suggest a role of high SSG in adaptation of herbaceous plants to water stress (e.g. Lens et al 2016) in addition to woody plants that have been featured in most previous investigations.…”
Section: Stem Specific Gravitymentioning
confidence: 55%
“…Plants with dense wood may be more resistant to xylem cavitation, thus are well adapted to drought compared to species with porous, low density wood (Pockman and Sperry 2000;Hacke et al 2001;Chave et al 2009). Our study extends the use of SSG beyond woody plants to herbaceous plants, in which cavitation resistance also has been associated with stem tissue density (Wahl and Ryer 2000;Lens et al 2016). Also, we investigated plot coverage by species with the C4 photosynthetic pathway, which are mostly grasses in our study, because the C4 pathway confers greater photosynthetic rate and water use efficiency in semiarid areas with high irradiance and mean temperature (Doliner and Jolliffe 1979;Teeri and Stowe 1976;Kemp 1983).…”
Section: Trait Datamentioning
confidence: 99%
“…Similar ontogenic changes in the resistance to xylem embolism have been observed in grapevine stems across the growing season (Charrier et al, ) as well as between juvenile and adult individuals of red oak (Cavender‐Bares & Bazzaz, ), laurel (Lamarque et al, ), and Tasmanian bluegum (Lucani, Brodribb, Jordan, & Mitchell, ). Although there is no clear explanation for these patterns, possible causes include increased lignification and changes in wood anatomical features through time (Lens et al, ; Li et al, ; Wheeler, Sperry, Hacke, & Hoang, ). Second, the wild type exhibited both higher stem hydraulic conductivity and greater resistance to xylem embolism, which suggests that there is no xylem safety‐efficiency trade‐off in the tomato lines we tested.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in plant hydraulics have mainly focused on woody species, but newly developed imaging tools such as X‐ray microtomography (Cochard, Delzon, & Badel, ) and the optical vulnerability technique (Brodribb et al, ) allow for a better understanding of the thresholds of vulnerability to water deficit in herbaceous species. Some herbaceous grasses have been found to be more resistant to embolism than previously thought: the xylem pressure inducing a 50% loss of hydraulic conductivity (Ψ 50 ) ranged from −0.5 MPa in reed canary grass ( Phallaris arundinacea ) to −7.5 MPa in European feather grass ( Stipa pennata ; Lens et al, ). The few estimates of crop Ψ 50 available so far range from −1.6 MPa in rice (Stiller, Lafitte, & Sperry, ) to −3 MPa in sunflower (Ahmad et al, ), but embolism resistance can vary significantly between different varieties within a crop species (Ahmad et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been few assessments of vulnerability to embolism in herbaceous plants (Cochard et al , Mencuccini and Comstock , Saha et al , Lens et al ). Lens et al () showed that herbaceous plants are generally more resistant to embolism than previously thought and that they do not routinely experience xylem embolism.…”
Section: Introductionmentioning
confidence: 99%